Size effect of mechanical characteristics of sandstone and granite under uniaxial compression - Kong, Lulin; Wu, Jie; Wang, Haige; Shi, Xiangchao; Gao, Leiyu; Zhuo, Xiao; Chen, Shuai (Frontiers in Energy Research, 2023)
The accurate evaluation of the mechanical properties of rocks is crucial to the design of large-scale projects, such as the construction of dams and bridges, the excavation of tunnels, and petroleum engineering research. In this study, experiments pertaining to the size effect of sandstone and granite were performed on small square samples of 10–25 mm. It was found that the elastic modulus of sandstone and granite decreases significantly with increasing size. The uniaxial compressive strength, however, follows a different trend. When the size of the sample increases from 10 to 25 mm, the uniaxial compressive strength of sandstone increases by approximately 12%. However, the strength of granite decreases by 35% as the size increases. The discrepancies in the failure of sandstone and granite are apparent, and the failure patterns of the same rock do not vary with size. Sandstone mostly suffers from split damage, whereas granite mainly suffers from shear failure. Contemporary studies have found that the mechanical properties of rocks are closely related to the sizes of the samples. However, these studies have primarily focused on the size effect of rocks, whose samples sizes were greater than 30 mm in diameter. The understanding constructs the relationship between the strength transformation of different sizes of rocks, which is of great significance for practical engineering applications.